Deleuze: History and Science - DeLanda, Manuel (New York Atropos, 2010)
This is a collection of essays, most published here for the first time, on Gilles Deleuze's ideas about history and science. Its focus is on ontological or metaphysical questions: What are the legitimate social entities that can be used in historical explanations, given a materialist metaphysics? What are the legitimate inhabitants of the material world, natural and artificial, and what role should science play in determining their legitimacy? What can philosophy contribute to this enterprise? --- Manuel DeLanda is the author of five philosophy books, War in the Age of Intelligent Machines (1991), A Thousand Years of Nonlinear History (1997), Intensive Science and Virtual Philosophy (2002), A New Philosophy of Society (2006) , and The Emergence of Synthetic Reason (Forthcoming). He teaches two seminars at University of Pennsylvania, Department of Architecture: "Philosophy of History: Theories of Self-Organization and Urban Dynamics", and "Philosophy of Science: Thinking about Structures and Materials". He also holds the Gilles Deleuze chair at the European Graduate School in Saas-Fee, Switzerland.
Keywords: Philosophy; History